2023
DOI: 10.1063/5.0162597
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap for focused ion beam technologies

Katja Höflich,
Gerhard Hobler,
Frances I. Allen
et al.

Abstract: The focused ion beam (FIB) is a powerful tool for fabrication, modification, and characterization of materials down to the nanoscale. Starting with the gallium FIB, which was originally intended for photomask repair in the semiconductor industry, there are now many different types of FIB that are commercially available. These instruments use a range of ion species and are applied broadly in materials science, physics, chemistry, biology, medicine, and even archaeology. The goal of this roadmap is to provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 1,097 publications
0
5
0
Order By: Relevance
“…Fabrication process of the sensor shows in the figure 18 [35][36][37]. However, highly efficient etching techniques require high current beams, however, high current sources tend to deliver ions with large energy distributions, and a large number of ions will interact with the etched surface [40], resulting in damage to the surface of the nano-groove, which affects the experimental results. When etching more complex structures, it is inevitable that some errors will occur, causing the geometry of the device to be altered, which will also have an impact on the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication process of the sensor shows in the figure 18 [35][36][37]. However, highly efficient etching techniques require high current beams, however, high current sources tend to deliver ions with large energy distributions, and a large number of ions will interact with the etched surface [40], resulting in damage to the surface of the nano-groove, which affects the experimental results. When etching more complex structures, it is inevitable that some errors will occur, causing the geometry of the device to be altered, which will also have an impact on the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the maskless site-selective writing of nanostructures with the desired shape and dimension using focused electron/ion beams is a powerful tool for bottom-up nanofabrication. While a large variety of approaches based on additive manufacturing have reached a high level of sophistication for objects down to the lower micrometer range, challenges remain for the preparation of 3D nanostructures. , The general trend of miniaturization of devices and functional 1D–3D structures requires continuous progress enabling the development of novel applications due to specific functionalities emerging at the nanoscale (e.g., plasmonics, magnetic phenomena). , Therefore, both techniques, focused- electron-beam- and focused-ion-beam-induced deposition (FEBID/FIBID), are of particular interest. General introductions to the subject, including the physics of beam–substrate interactions ,, and suitable precursors for FEBID/FIBID, are available. The main differences between the exclusively additive FEBID and the more complex FIBID are the incorporation of ions into the growing material, implantation into the substrate, and damage to the substrate material either by amorphization or localized sputtering of the substrate/deposit due to the momentum transfer of the ions. , For example, Ga + ion sources inherently result in the incorporation of Ga into the growing material and thus in a material composition that is dependent on the growth rate. Inadvertent incorporation of the ion source material into the deposit can be prevented by using alternatives such as gas field ion source processing for FIBID. , While similar effects occur for different ions, the specific contributions to sputtering, energy transfer, and fragmentation efficiency of precursor moieties is determined by ion mass, size, and energy. , …”
Section: Introductionmentioning
confidence: 99%
“… 4 , 9 19 Therefore, both techniques, focused- electron-beam- and focused-ion-beam-induced deposition (FEBID/FIBID), are of particular interest. General introductions to the subject, including the physics of beam–substrate interactions 6 , 20 , 21 and suitable precursors for FEBID/FIBID, 22 24 are available. The main differences between the exclusively additive FEBID and the more complex FIBID are the incorporation of ions into the growing material, implantation into the substrate, and damage to the substrate material either by amorphization or localized sputtering of the substrate/deposit due to the momentum transfer of the ions.…”
Section: Introductionmentioning
confidence: 99%
“…Focused ion-beam-induced deposition (FIBID) of organometallic precursors is a charged particle, bottom-up technique capable of directly fabricating metal-containing nanostructures. Some of the differences between FIBID and focused electron beam-induced deposition (FEBID) are that FIBID has higher current densities leading to more rapid deposition rates, produces deposits with higher metal contents than FEBID, and has a wider choice of charged particle sources. Differences in the microstructures of FIBID and FEBID materials have also been reported. For example, in a recent comparative FIBID/FEBID study using the metal silicide precursor H 2 Si­(Co­(CO) 4 ) 2 , it has been observed that the FIBID material is typically porous, while a measurably more dense deposit is obtained by FEBID .…”
Section: Introductionmentioning
confidence: 99%